Preparation method of high-thermal-conductivity C / SiC-ZrB2 composite material with three-dimensional interpenetrating network structure characteristics and high-thermal-conductivity C / SiC-ZrB2 composite material
By constructing a three-dimensional interpenetrating network structure with a high thermal conductivity C/SiC-ZrB2 composite material, the problem of high difficulty in braiding process of mesophase asphalt-based fiber prefabricated body is solved, and the high thermal conductivity and structural stability is improved, which is suitable for applications in high temperature environments.
Patent Information
- Application Number
- CN202411939456.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, the weaving process of the mesophase asphalt-based fiber preform is difficult, and it is difficult to obtain a high thermal conductivity three-way orthogonal preform.
The mixed fibers are formed by mixing asphalt-based carbon fibers and aramid fibers. After heat treatment, PyC pyrolytic carbon layer deposition, carbon nanotube interface growth and SiC layer deposition, a three-dimensional interpenetrating network structure is constructed to form a highly thermally conductive C/SiC-ZrB2 composite material.
It realizes a three-dimensional interpenetrating network structure with high thermal conductivity and structural stability, improves the thermal conductivity and ablation resistance of ceramic matrix composite materials, and is suitable for heat dissipation and aerospace fields under high temperature environments.
Smart Images

Figure CN119797951A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a composite material, and in particular to a method for preparing a composite material having a three-dimensional interpenetrating network structure and a high thermal conductivity C / SiC-ZrB 2 Preparation method of composite material and high thermal conductivity C / SiC-ZrB 2 Composite materials. Background Art
[0002] As hypersonic vehicles have increasingly higher requirements for lightweight structure, efficient heat transfer and heat dissipation, and thermal dimensional stability, it has become an urgent need to expand the extreme environment resistance of existing thermal protection systems and their materials and explore new thermal protection material systems to promote the development of hypersonic and aerospace vehicle technologies. Traditional ceramic-based materials are prone to thermal stress concentration in high-temperature environments due to their relatively low thermal conductivity, which in turn causes material cracking or failure, limiting their application in high-temperature environments. High thermal conductivity mesophase asphalt-based carbon fibers have the advantages of high thermal conductivity, ultra-high modulus, low density, and low thermal expansion coefficient. However, due to the influence of their own modulus, the weaving process of mesophase asphalt-based fiber preforms is difficult. When Li Baoliu and others from Hunan University prepared a three-dimensional orthogonal preform, they used high thermal conductivity asphalt-based fibers in the X and Y directions, and low modulus PAN-based fibers in the Z direction. The PAN-based fibers have poor thermal conductivity, so the thermal conductivity of the three-dimensional orthogonal preform structure in the Z direction is limited. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that the weaving process of the mesophase pitch-based fiber preform in the prior art is difficult and it is difficult to obtain a high thermal conductivity three-dimensional orthogonal preform, and to provide a high thermal conductivity C / SiC-ZrB 2 Preparation method of composite material and high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0004] To achieve the above objectives, the technical solutions provided by the present invention are as follows:
[0005] A high thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure 2 The preparation method of the composite material is special in that it comprises the following steps:
[0006] S1, mixing pitch-based carbonized fibers and aramid fibers to form mixed fibers, and using the mixed fibers to prepare a first high thermal conductivity fiber preform;
[0007] S2, heat-treating the first high thermal conductivity fiber preform to obtain a second high thermal conductivity fiber preform;
[0008] S3, depositing a PyC pyrolytic carbon layer on the second high thermal conductivity fiber preform to obtain a third high thermal conductivity fiber preform;
[0009] S4, growing a carbon nanotube interface on the third high thermal conductivity fiber preform to obtain a fourth high thermal conductivity fiber preform;
[0010] S5, sequentially depositing a PyC pyrolytic carbon layer and a SiC layer on the fourth high thermal conductivity fiber preform to obtain a high thermal conductivity C / SiC composite material;
[0011] S6, add ZrB to the phenolic resin solution with a mass fraction of 10% to 20% 2 The particles and SiC particles are ball-milled to obtain a first slurry;
[0012] S7, using the first slurry to perform ultra-high temperature modification on the high thermal conductivity C / SiC composite material obtained in step S5 to obtain a porous high thermal conductivity C / SiC-ZrB 2 Composite materials;
[0013] S8, the high thermal conductivity C / SiC-ZrB obtained in step S7 2 After the composite material is subjected to liquid silicon infiltration reaction, a densified high thermal conductivity C / SiC-ZrB 2 The composite material is prepared.
[0014] Further, step S7 is specifically as follows:
[0015] S7.1. Under vacuum conditions, the high thermal conductivity C / SiC composite material is immersed in the first slurry;
[0016] S7.2. curing the high thermal conductivity C / SiC composite material and performing a cracking treatment;
[0017] S7.3. Under vacuum conditions, the high thermal conductivity C / SiC composite material is immersed in a phenolic resin solution with a mass fraction of 20% to 30%, and then cured and cracked to obtain a porous high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0018] Furthermore, in step S1, the density of the mixed fiber is 0.7-0.9 g / cm 3 , porosity is 55% to 75%;
[0019] In step S3, the thickness of the PyC pyrolytic carbon layer is 500-1000 nm;
[0020] In step S5, the thickness of the PyC pyrolytic carbon layer is 1000-2000 nm.
[0021] Furthermore, step S7.1 is specifically as follows:
[0022] The first slurry is added into a pressure impregnation tank, the high thermal conductivity C / SiC composite material obtained in step S5 is hung above the first slurry, the pressure impregnation tank is sealed and evacuated, and then the high thermal conductivity C / SiC composite material is immersed in the first slurry for impregnation.
[0023] Furthermore, in step S7.1, the immersion is specifically: maintaining the vacuum condition for 0.5 to 1 hour, then pressurizing to 0.5 MPa to 1.4 MPa, maintaining the pressure for 0.5 to 1 hour, and then taking out;
[0024] Step S7.2 is specifically as follows: curing the high thermal conductivity C / SiC composite material at 50-150°C for 2-6 hours, then maintaining the temperature at 900-1200°C for 1-3 hours in a vacuum environment for cracking treatment, and then cooling to room temperature.
[0025] Furthermore, step S7.3 is specifically as follows:
[0026] Add 20% to 30% phenolic resin solution into the pressure impregnation tank to impregnate the high thermal conductivity C / SiC-ZrB 2 The composite material is suspended above the phenolic resin solution, and the sealed pressure impregnation tank is evacuated to form a high thermal conductivity C / SiC-ZrB 2 The composite material is immersed in a phenolic resin solution, maintained under vacuum conditions for 0.5 to 1 hour, then pressurized to 0.5 MPa to 1.4 MPa and maintained under pressure for 0.5 to 1 hour before being taken out, cured at 50 to 150 ° C for 2 to 6 hours, then kept at 900 to 1200 ° C for 1 to 3 hours under vacuum for cracking treatment, and then cooled to room temperature to obtain a porous high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0027] Furthermore, step S2 is specifically as follows:
[0028] S2.1. In a protective atmosphere, the temperature is raised to 900-1000°C at a heating rate of 3-5°C / min, and kept at this temperature for 1-2h to heat treat the first high thermal conductivity fiber preform, and then cooled to room temperature; the flow rate of the protective atmosphere is 10-100mL / min;
[0029] S2.2. In a protective atmosphere, raise the temperature to 2600-3000°C at a heating rate of 3-5°C / min, keep it warm for 1-2 hours to heat-treat the first high thermal conductivity fiber preform, and then cool it to room temperature to obtain a second high thermal conductivity fiber preform; the flow rate of the protective atmosphere is 10-100mL / min.
[0030] Furthermore, step S4 is specifically as follows:
[0031] In a protective atmosphere, the temperature is raised to 1000-1200° C. at a heating rate of 3-5° C. / min, kept at that temperature for 1-3 hours, and then lowered to room temperature, thereby growing a carbon nanotube interface on the third high thermal conductivity fiber preform to obtain a fourth high thermal conductivity fiber preform; the protective atmosphere flow rate is 10-100 mL / min;
[0032] In steps S2.1, S2.2 and S4, the protective atmosphere is nitrogen;
[0033] In step S6, the ZrB 2 The particle size of the particles and SiC particles is 1 to 5 μm, the total volume fraction is 5% to 15% of the phenolic resin solution, and the ball milling time is 12 to 15 hours;
[0034] Step S8 is specifically: the porous high thermal conductivity C / SiC-ZrB obtained in step S7.3 is 2 After the composite material is wrapped with Si powder, it is placed in a siliconizing furnace and subjected to liquid silicon melt infiltration reaction at 1430-1550°C in a vacuum environment for 1-3 hours to obtain a densified high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0035] Further, in step S2.1, the temperature was raised to 940°C at a heating rate of 3°C / min, and kept at that temperature for 1.5h, and the flow rate of the protective atmosphere was 80mL / min;
[0036] In step S2.2, the temperature was raised to 2800°C at a heating rate of 5°C / min and kept at that temperature for 1.5h, and the flow rate of the protective atmosphere was 80mL / min;
[0037] In step S4, the temperature is raised to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2h, and the protective atmosphere flow rate is 100mL / min;
[0038] In step S6, the ZrB 2 The particle size of the particles and SiC particles was 3 μm, the total volume fraction was 12% of the phenolic resin solution, and the ball milling time was 12 hours;
[0039] In step S7.1, the vacuum condition is maintained for 0.5 hours, and then the pressure is increased to 0.8 MPa, and the pressure is maintained for 0.5 hours before removal;
[0040] In step S7.2, the high thermal conductivity C / SiC composite material is cured at 90°C for 4 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment;
[0041] In step S7.3, the mass fraction of the phenolic resin solution is 24%; the high thermal conductivity C / SiC-ZrB 2The composite material was immersed in a phenolic resin solution, maintained under vacuum conditions for 1 hour, then pressurized to 1.2 MPa and maintained under pressure for 1 hour before being taken out, cured at 90°C for 3 hours, and then maintained at 1000°C for 2 hours under vacuum conditions for cracking treatment;
[0042] In step S8, liquid silicon infiltration reaction is performed in a vacuum environment at 1500° C. for 2 hours.
[0043] At the same time, the present invention also provides a high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure. 2 High thermal conductivity C / SiC-ZrB prepared by preparation method of composite material 2 Composite materials.
[0044] Beneficial effects of the present invention:
[0045] 1. The high thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure of the present invention 2 Preparation method of composite materials, the asphalt-based carbonized fiber in the mixed fiber has strong thermal stability, can maintain good structural and performance stability under high temperature environment, and can form a highly ordered graphite structure after heat treatment and graphitization, forming a high thermal conductivity fiber framework. After the first high thermal conductivity fiber preform is heat treated, firstly, the thermal conductivity of the ceramic matrix composite interface is improved by introducing high thermal conductivity carbon nanotubes, and secondly, by depositing PyC pyrolytic carbon layer and SiC layer, a three-dimensional CNT@PyC@SiC matrix is constructed to adjust the pore size inside the preform, and finally, by using multi-component particles ZrB 2 The particles and SiC particles regulate the stress adaptability between the matrix and further improve the ablation resistance of the ceramic matrix composites at higher temperatures.
[0046] 2. The high thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure of the present invention 2 The preparation method of the composite material vapor-grows the carbon nanotube interface on the fiber surface, constructs a highly interconnected thermal conductive network between the fiber and the matrix, can improve the bonding performance of the interface and the fiber, improve the interface bonding between the fiber and the matrix, enhance the structural stability of the composite material, and optimize the thermal conduction path, thereby improving the heat conduction channel, reducing thermal resistance, and forming a three-dimensional thermal conductive network between the fiber and the matrix material.
[0047] 3. The high thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure of the present invention 2 The preparation method of the composite material is to introduce ZrB 2 , SiC and other multi-element ultra-high temperature materials can not only improve the material's high temperature resistance and ablation resistance in extreme environments, but also effectively improve the thermal expansion matching between particles and reduce the thermal stress of the matrix under high temperature.
[0048] 4. The high thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure of the present invention 2 The three-dimensional CNTs@PyC@SiC matrix constructed by the composite material preparation method can effectively divide the macropores between bundles and ZrB 2 The particles and the matrix formed by SiC particles form a strong interface, which effectively prevents crack propagation and improves the bending strength of the material.
[0049] 5. High thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure characteristics of the present invention 2 The preparation method of the composite material can further adjust the density of the mixed fiber, the growth conditions of the carbon nanotube interface, the ZrB 2 The ratio of the ultra-high temperature ceramic phase formed by the particles and SiC particles, as well as other process parameters, are combined with technology to ensure the uniformity and continuity of the material at the macro and micro scales, achieve precise control of material properties, and make the composite material preparation process flexible and efficient.
[0050] 6. High thermal conductivity C / SiC-ZrB of the present invention 2 The composite material has excellent thermal conductivity and mechanical properties. The out-of-plane thermal conductivity can reach 103.46W / (Km), and the bending mechanical properties can reach 199.50MPa. Compared with the existing C / SiC-ZrB 2 Composite materials have significantly improved performance and are suitable for heat dissipation, thermal management, aerospace and other fields in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure of the present invention 2 Flow chart of Example 1 of the preparation method of the composite material;
[0052] Figure 2 The high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure of the present invention 2 A macroscopic image of the first high thermal conductivity fiber preform in Example 1 of the method for preparing a composite material;
[0053] Figure 3 The high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure of the present invention 2 A microscopic morphology of a fiber cross section of the second high thermal conductivity fiber preform in Example 1 of the preparation method of the composite material;
[0054] Figure 4 The high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure of the present invention 2Microscopic morphology of carbon nanotubes on the fourth high thermal conductivity fiber preform in Example 1 of the preparation method of the composite material;
[0055] Figure 5 The high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure of the present invention 2 Preparation method of composite material Example 1 A microscopic morphology of the three-dimensional CNTs@PyC@SiC matrix structure magnified 100 times;
[0056] Figure 6 The high thermal conductivity C / SiC-ZrB having a three-dimensional interpenetrating network structure of the present invention 2 Preparation method of composite material Example 1 A microscopic morphology of the three-dimensional CNTs@PyC@SiC matrix structure magnified 150 times;
[0057] Figure 7 The high thermal conductivity C / SiC-ZrB 2 Three-point bending mechanical properties test results of composite material embodiment 1. DETAILED DESCRIPTION
[0058] Embodiment 1
[0059] In order to give full play to the electrical and thermal conductivity of mesophase pitch-based carbon fibers and overcome their shortcomings of high modulus and poor weaving performance, the present invention uses low modulus, carbonized pitch-based fibers with a certain strength and aramid fibers with high strength and excellent flexibility to mix and weave, and finally form a three-dimensional orthogonal pitch-based carbon fiber preform with high thermal conductivity pitch-based carbon fibers in the XYZ direction after carbonization and graphitization. This structure is expected to meet the stringent requirements of hypersonic vehicles on the mechanical properties and thermal conductivity of composite materials while maintaining high performance.
[0060] High thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure characteristics of the present invention 2 The preparation process of the composite material is as follows Figure 1 As shown, the specific steps include:
[0061] Step 1: 2K mixed fiber is formed by mixing asphalt-based carbonized fiber and aramid fiber, and its density is about 0.82g / cm 3 , the porosity is 62%, and the first high thermal conductivity fiber preform is prepared according to the design requirements using the mixed fiber, such as Figure 2 shown.
[0062] Step 2: heat-treating the first high thermal conductivity fiber preform in a nitrogen protective atmosphere. The heat treatment parameters are: raising the temperature to 940° C. at a heating rate of 3° C. / min, keeping the temperature for 1.5 hours, and then lowering the temperature to room temperature. The flow rate of the protective atmosphere is 80 mL / min.
[0063] Step 3, heat-treating the first high thermal conductivity fiber preform in a nitrogen protective atmosphere to obtain a second high thermal conductivity fiber preform, such as Figure 3 The heat treatment parameters are as follows: the temperature is raised to 2800°C at a heating rate of 5°C / min, kept at that temperature for 1.5h, then dropped to room temperature, and the flow rate of the protective atmosphere is 80mL / min.
[0064] Step 4: depositing a PyC pyrolytic carbon layer with a thickness of 700 nm on the second high thermal conductivity fiber preform by a chemical vapor infiltration process (CVI process) to obtain a third high thermal conductivity fiber preform.
[0065] Step 5, in a nitrogen protective atmosphere, a carbon nanotube interface is grown on the third high thermal conductivity fiber preform by a chemical vapor deposition process (CVD process) to obtain a fourth high thermal conductivity fiber preform, such as Figure 4 As shown, the parameters for growing the carbon nanotube interface are as follows: raising the temperature to 1000° C. at a heating rate of 5° C. / min, keeping the temperature for 2 h, and then lowering the temperature to room temperature, and the protective atmosphere flow rate is 100 mL / min.
[0066] Step 6: Using the CVI process, a 1600 nm thick PyC pyrolytic carbon layer is deposited on the fourth high thermal conductivity fiber preform, and then a SiC layer is deposited on the PyC pyrolytic carbon layer by the CVI process to form a three-dimensional CNTs@PyC@SiC matrix. Figure 5 and Figure 6 As shown, a high thermal conductivity C / SiC composite material is obtained.
[0067] Step 7: weigh phenolic resin powder and solvent according to the ratio to prepare a phenolic resin solution with a mass fraction of 15%, and add ZrB with a particle size of 3 μm and a volume fraction of 12% to the phenolic resin solution. 2 The particles and SiC particles are ball-milled for 12-15 hours to prepare a first slurry.
[0068] Step 8, hang the high thermal conductivity C / SiC composite material prepared in step 6 above the first slurry in a pressure impregnation tank and evacuate to ensure that the air in the high thermal conductivity C / SiC composite material is completely extracted, then immerse it in the first slurry, maintain the vacuum condition for 0.5 hour, then pressurize to 0.8 MPa and maintain the pressure for 0.5 hour to take out the high thermal conductivity C / SiC composite material.
[0069] Step 9, curing the impregnated high thermal conductivity C / SiC composite material at 90° C. for 4 hours, then keeping it at 1000° C. for 2 hours in a vacuum environment for cracking treatment, and then cooling it to room temperature.
[0070] Step 10, suspending the cured and cracked high thermal conductivity C / SiC composite material above a phenolic resin solution with a mass fraction of 24% in a pressure impregnation tank, evacuating the solution, and then immersing the solution in the phenolic resin solution, maintaining the vacuum condition for 1 hour, and then pressurizing to 1.2 MPa and maintaining the pressure for 1 hour before taking it out, curing it at 90° C. for 3 hours, and then maintaining the temperature at 1000° C. for 2 hours in a vacuum environment for cracking treatment, and then cooling it to room temperature to obtain a porous high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0071] Step 11, the porous high thermal conductivity C / SiC-ZrB obtained in step 10 2 After the composite material was wrapped with Si powder, it was placed in a siliconizing furnace and subjected to liquid silicon melt infiltration (RMI) for 2 hours at 1500℃ in a vacuum environment, and then cooled to room temperature to obtain a densified high thermal conductivity C / SiC-ZrB 2 Composite materials. The results of mechanical properties test are as follows Figure 7 As shown in Table 1, three points on the surface (respectively named Spot1, Spot2 and Spot3) were taken to test the thermal diffusion coefficient and thermal conductivity. 2 The thermal conductivity of the composite material is usually 10-20W / (mK), so it can be seen that the high thermal conductivity C / SiC-ZrB 2 The thermal conductivity of the composite material is higher than that of the existing C / SiC-ZrB 2 Composite materials have improved significantly.
[0072] Table 1 Thermal diffusivity and thermal conductivity of composite materials at room temperature
[0073]
[0074] The above steps 7-9 are ultra-high temperature modification processes. The present invention uses phenolic resin solution as a solvent to dissolve ZrB 2 and SiC particles to form a first slurry with a higher viscosity, which is convenient for increasing the residence time of the first slurry on the high thermal conductivity C / SiC composite material in the subsequent steps, thereby increasing the ZrB 2 The retention rate of SiC is increased, the number of impregnations is reduced, and the preparation efficiency is improved. At the same time, the phenolic resin is converted into carbon retention during the cracking process, avoiding the subsequent preparation of the carbon matrix again, simplifying the preparation process. In the present invention, the negative pressure after vacuuming is usually -0.1MPa.
[0075] Embodiment 2
[0076] High thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure characteristics of the present invention 2 The preparation method of the composite material comprises the following steps:
[0077] Step 1: 2K mixed fiber is formed by mixing asphalt-based carbonized fiber and aramid fiber, and its density is about 0.7g / cm 3 , the porosity is 75%, and the first high thermal conductivity fiber preform is prepared according to the design requirements using the mixed fiber.
[0078] Step 2: heat-treating the first high thermal conductivity fiber preform in a nitrogen protective atmosphere. The heat treatment parameters are: raising the temperature to 900° C. at a heating rate of 5° C. / min, keeping the temperature for 2 hours, and then lowering the temperature to room temperature. The flow rate of the protective atmosphere is 10 mL / min.
[0079] Step 3: heat-treating the first high thermal conductivity fiber preform in a nitrogen protective atmosphere to obtain a second high thermal conductivity fiber preform. The heat treatment parameters are: raising the temperature to 3000°C at a heating rate of 4°C / min, keeping the temperature for 1 hour, and then lowering the temperature to room temperature. The flow rate of the protective atmosphere is 10 mL / min.
[0080] Step 4: depositing a 500 nm thick PyC pyrolytic carbon layer on the second high thermal conductivity fiber preform by a CVI process to obtain a third high thermal conductivity fiber preform.
[0081] Step 5, in a nitrogen protective atmosphere, growing a carbon nanotube interface on the third high thermal conductivity fiber preform by a CVD process to obtain a fourth high thermal conductivity fiber preform, and the specific parameters for growing the carbon nanotube interface are: raising the temperature to 1100°C at a heating rate of 3°C / min, keeping it warm for 1h, and then dropping it to room temperature, and the protective atmosphere flow rate is 10mL / min.
[0082] Step 6: Use the CVI process to deposit a 2000 nm thick PyC pyrolytic carbon layer on the fourth high thermal conductivity fiber preform, and then deposit a SiC layer on the PyC pyrolytic carbon layer by the CVI process to form a three-dimensional CNTs@PyC@SiC matrix to obtain a high thermal conductivity C / SiC composite material.
[0083] Step 7: weigh phenolic resin powder and solvent according to the ratio to prepare a phenolic resin solution with a mass fraction of 10%, and add ZrB with a particle size of 5 μm and a volume fraction of 15% to the phenolic resin solution. 2 The particles and SiC particles are ball-milled for 12 hours to prepare a first slurry.
[0084] Step 8, hang the high thermal conductivity C / SiC composite material prepared in step 6 above the first slurry in a pressure impregnation tank and evacuate to ensure that the air in the high thermal conductivity C / SiC composite material is completely extracted, then immerse it in the first slurry, maintain the vacuum condition for 0.5 hour, then pressurize to 0.5 MPa and maintain the pressure for 1 hour to take out the high thermal conductivity C / SiC composite material.
[0085] Step 9, curing the impregnated high thermal conductivity C / SiC composite material at 50° C. for 6 hours, then keeping it at 900° C. for 1 hour in a vacuum environment for cracking treatment, and then cooling it to room temperature.
[0086] Step 10, suspending the cured and cracked high thermal conductivity C / SiC composite material above a phenolic resin solution with a mass fraction of 20% in a pressure impregnation tank, evacuating the solution, and then immersing the solution in the phenolic resin solution, maintaining the vacuum condition for 1 hour, and then pressurizing to 0.5 MPa and maintaining the pressure for 0.5 hour, taking it out, curing it at 150° C. for 2 hours, and then maintaining the temperature at 900° C. for 1 hour in a vacuum environment for cracking treatment, and then cooling it to room temperature to obtain a porous high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0087] Step 11, the porous high thermal conductivity C / SiC-ZrB obtained in step 10 2 After the composite material was wrapped with Si powder, it was placed in a siliconizing furnace and subjected to liquid silicon melt infiltration reaction at 1430°C in a vacuum environment for 1 hour, and then cooled to room temperature to obtain a densified high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0088] Embodiment 3
[0089] High thermal conductivity C / SiC-ZrB with three-dimensional interpenetrating network structure characteristics of the present invention 2 The preparation method of the composite material comprises the following steps:
[0090] Step 1: 2K mixed fiber is formed by mixing asphalt-based carbonized fiber and aramid fiber, and its density is about 0.9g / cm 3 , the porosity is 55%, and the first high thermal conductivity fiber preform is prepared according to the design requirements using the mixed fiber.
[0091] Step 2: heat-treating the first high thermal conductivity fiber preform in a nitrogen protective atmosphere. The heat treatment parameters are: raising the temperature to 1000° C. at a heating rate of 4° C. / min, keeping the temperature for 1 hour, and then lowering the temperature to room temperature. The flow rate of the protective atmosphere is 50 mL / min.
[0092] Step 3: heat-treating the first high thermal conductivity fiber preform in a nitrogen protective atmosphere to obtain a second high thermal conductivity fiber preform. The heat treatment parameters are: raising the temperature to 2600°C at a heating rate of 3°C / min, keeping the temperature for 2 hours, and then lowering it to room temperature. The flow rate of the protective atmosphere is 100 mL / min.
[0093] Step 4: depositing a PyC pyrolytic carbon layer with a thickness of 1000 nm on the second high thermal conductivity fiber preform by a CVI process to obtain a third high thermal conductivity fiber preform.
[0094] Step 5, in a nitrogen protective atmosphere, growing a carbon nanotube interface on the third high thermal conductivity fiber preform by a CVD process to obtain a fourth high thermal conductivity fiber preform, and the specific parameters for growing the carbon nanotube interface are: raising the temperature to 1200°C at a heating rate of 4°C / min, keeping it warm for 3 hours, and then dropping it to room temperature, and the protective atmosphere flow rate is 50mL / min.
[0095] Step 6: Use the CVI process to deposit a 1000 nm thick PyC pyrolytic carbon layer on the fourth high thermal conductivity fiber preform, and then deposit a SiC layer on the PyC pyrolytic carbon layer by the CVI process to form a three-dimensional CNTs@PyC@SiC matrix to obtain a high thermal conductivity C / SiC composite material.
[0096] Step 7: weigh phenolic resin powder and solvent according to the ratio to prepare a phenolic resin solution with a mass fraction of 20%, and add ZrB with a particle size of 1 μm and a volume fraction of 5% to the phenolic resin solution. 2 The particles and SiC particles are ball-milled for 12 hours to prepare a first slurry.
[0097] Step 8, hang the high thermal conductivity C / SiC composite material prepared in step 6 above the first slurry in a pressure impregnation tank and evacuate to ensure that the air in the high thermal conductivity C / SiC composite material is completely extracted, then immerse it in the first slurry, maintain the vacuum condition for 1 hour, then pressurize to 1.4 MPa and maintain the pressure for 0.5 hour to take out the high thermal conductivity C / SiC composite material.
[0098] Step 9, curing the impregnated high thermal conductivity C / SiC composite material at 150° C. for 2 hours, then keeping it at 1200° C. for 3 hours in a vacuum environment for cracking treatment, and then cooling it to room temperature.
[0099] Step 10, suspending the cured and cracked high thermal conductivity C / SiC composite material above a 30% by mass phenolic resin solution in a pressure impregnation tank, evacuating the solution, and then immersing the solution in the phenolic resin solution, maintaining the vacuum condition for 0.5 hours, then pressurizing to 1.4 MPa and maintaining the pressure for 0.5 hours, taking it out, curing it at 50° C. for 6 hours, then maintaining the temperature at 1200° C. for 3 hours in a vacuum environment for cracking treatment, and then cooling it to room temperature to obtain a porous high thermal conductivity C / SiC-ZrB 2 Composite materials.
[0100] Step 11, the porous high thermal conductivity C / SiC-ZrB obtained in step 10 2 After the composite material was wrapped with Si powder, it was placed in a siliconizing furnace and subjected to liquid silicon melt infiltration reaction at 1550℃ in a vacuum environment for 3 hours, and then cooled to room temperature to obtain a densified high thermal conductivity C / SiC-ZrB 2 Composite materials.
Claims
1. A method for preparing a high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure, characterized in that: The following steps are involved: S1, mixing pitch-based carbonized fibers and aramid fibers to form mixed fibers, and using the mixed fibers to prepare a first high thermal conductivity fiber preform; S2, heat-treating the first high thermal conductivity fiber preform to obtain a second high thermal conductivity fiber preform; S3, depositing a PyC pyrolytic carbon layer on the second high thermal conductivity fiber preform to obtain a third high thermal conductivity fiber preform; S4, growing a carbon nanotube interface on the third high thermal conductivity fiber preform to obtain a fourth high thermal conductivity fiber preform; S5, sequentially depositing a PyC pyrolytic carbon layer and a SiC layer on the fourth high thermal conductivity fiber preform to obtain a high thermal conductivity C / SiC composite material; S6, adding ZrB2 particles and SiC particles to a phenolic resin solution having a mass fraction of 10% to 20%, and ball milling to obtain a first slurry; S7, using the first slurry to perform ultra-high temperature modification on the high thermal conductivity C / SiC composite material obtained in step S5 to obtain a porous high thermal conductivity C / SiC-ZrB2 composite material; S8, subjecting the high thermal conductivity C / SiC-ZrB2 composite material obtained in step S7 to liquid silicon infiltration reaction to obtain a densified high thermal conductivity C / SiC-ZrB2 composite material, thereby completing the preparation.
2. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure according to claim 1, characterized in that: Step S7 is specifically as follows: S7.
1. Under vacuum conditions, the high thermal conductivity C / SiC composite material is immersed in the first slurry; S7.
2. curing the high thermal conductivity C / SiC composite material and performing a cracking treatment; S7.
3. Under vacuum conditions, the high thermal conductivity C / SiC composite material is immersed in a phenolic resin solution with a mass fraction of 20% to 30%, and then cured and cracked to obtain a porous high thermal conductivity C / SiC-ZrB2 composite material.
3. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure according to claim 1, characterized in that: In step S1, the density of the mixed fiber is 0.7-0.9 g / cm 3 , porosity is 55% to 75%; In step S3, the thickness of the PyC pyrolytic carbon layer is 500-1000 nm; In step S5, the thickness of the PyC pyrolytic carbon layer is 1000-2000 nm.
4. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having three-dimensional interpenetrating network structure characteristics according to claim 2, characterized in that: Step S7.1 is specifically as follows: The first slurry is added into a pressure impregnation tank, the high thermal conductivity C / SiC composite material obtained in step S5 is hung above the first slurry, the pressure impregnation tank is sealed and evacuated, and then the high thermal conductivity C / SiC composite material is immersed in the first slurry for impregnation.
5. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure according to claim 4, characterized in that: In step S7.1, the immersion is specifically: maintaining the vacuum condition for 0.5 to 1 hour, then pressurizing to 0.5 MPa to 1.4 MPa, maintaining the pressure for 0.5 to 1 hour, and then taking out; Step S7.2 is specifically as follows: curing the high thermal conductivity C / SiC composite material at 50-150°C for 2-6 hours, then maintaining the temperature at 900-1200°C for 1-3 hours in a vacuum environment for cracking treatment, and then cooling to room temperature.
6. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure according to claim 5, characterized in that: Step S7.3 is specifically as follows: A phenolic resin solution with a mass fraction of 20% to 30% is added into a pressure impregnation tank, a high thermal conductivity C / SiC-ZrB2 composite material is suspended above the phenolic resin solution, the pressure impregnation tank is sealed and evacuated, the high thermal conductivity C / SiC-ZrB2 composite material is immersed in the phenolic resin solution, the vacuum condition is maintained for 0.5 to 1 hour, then the pressure is increased to 0.5 MPa to 1.4 MPa and then the pressure is maintained for 0.5 to 1 hour before being taken out, cured at 50 to 150° C. for 2 to 6 hours, then kept at 900 to 1200° C. for 1 to 3 hours in a vacuum environment for cracking treatment, and then cooled to room temperature to obtain a porous high thermal conductivity C / SiC-ZrB2 composite material.
7. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having three-dimensional interpenetrating network structure characteristics according to claim 6, characterized in that: Step S2 is specifically as follows: S2.
1. In a protective atmosphere, the temperature is raised to 900-1000°C at a heating rate of 3-5°C / min, and kept at this temperature for 1-2h to heat treat the first high thermal conductivity fiber preform, and then cooled to room temperature; the flow rate of the protective atmosphere is 10-100mL / min; S2.
2. In a protective atmosphere, raise the temperature to 2600-3000°C at a heating rate of 3-5°C / min, keep it warm for 1-2 hours to heat-treat the first high thermal conductivity fiber preform, and then cool it to room temperature to obtain a second high thermal conductivity fiber preform; the flow rate of the protective atmosphere is 10-100mL / min.
8. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having three-dimensional interpenetrating network structure characteristics according to claim 7, characterized in that: Step S4 is specifically as follows: In a protective atmosphere, the temperature is raised to 1000-1200° C. at a heating rate of 3-5° C. / min, kept at that temperature for 1-3 hours, and then lowered to room temperature, thereby growing a carbon nanotube interface on the third high thermal conductivity fiber preform to obtain a fourth high thermal conductivity fiber preform; the protective atmosphere flow rate is 10-100 mL / min; In steps S2.1, S2.2 and S4, the protective atmosphere is nitrogen; In step S6, the particle size of the ZrB2 particles and the SiC particles is 1 to 5 μm, the total volume fraction is 5% to 15% of the phenolic resin solution, and the ball milling time is 12 to 15 hours; Step S8 is specifically as follows: after wrapping the porous high thermal conductivity C / SiC-ZrB2 composite material obtained in step S7.3 with Si powder, placing it in a siliconizing furnace, and performing liquid silicon melt infiltration reaction in a vacuum environment at 1430-1550°C for 1-3 hours to obtain a densified high thermal conductivity C / SiC-ZrB2 composite material.
9. The method for preparing the high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure according to claim 8, characterized in that: In step S2.1, the temperature was raised to 940°C at a heating rate of 3°C / min and kept at that temperature for 1.5h, and the flow rate of the protective atmosphere was 80mL / min; In step S2.2, the temperature was raised to 2800°C at a heating rate of 5°C / min and kept at that temperature for 1.5h, and the flow rate of the protective atmosphere was 80mL / min; In step S4, the temperature is raised to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2h, and the protective atmosphere flow rate is 100mL / min; In step S6, the particle size of the ZrB2 particles and the SiC particles is 3 μm, the total volume fraction is 12% of the phenolic resin solution, and the ball milling time is 12 hours; In step S7.1, the vacuum condition is maintained for 0.5 hours, and then the pressure is increased to 0.8 MPa, and the pressure is maintained for 0.5 hours before removal; In step S7.2, the high thermal conductivity C / SiC composite material is cured at 90°C for 4 hours, and then kept at 1000°C for 2 hours in a vacuum environment for cracking treatment; In step S7.3, the mass fraction of the phenolic resin solution is 24%; the high thermal conductivity C / SiC-ZrB2 composite material is immersed in the phenolic resin solution, maintained under vacuum conditions for 1 hour, then pressurized to 1.2 MPa and maintained under pressure for 1 hour before being taken out, cured at 90°C for 3 hours, and then kept at 1000°C for 2 hours under vacuum for cracking treatment; In step S8, liquid silicon infiltration reaction is performed in a vacuum environment at 1500° C. for 2 hours.
10. A high thermal conductivity C / SiC-ZrB2 composite material prepared by the method for preparing a high thermal conductivity C / SiC-ZrB2 composite material having a three-dimensional interpenetrating network structure as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Three-dimensional mesophase pitch-based carbon / carbon composite material with high heat conductivity and preparation technology thereof
CN103408315A
High-heat-dissipation HDPE (high-density polyethylene) electric conduit and preparation method thereof
CN114805984A
C / C-SiC-ZrC-ZrB2 composite material as well as preparation method and application thereof
CN116835989A
Method for preparing carbon-ceramic brake material and method for preparing carbon-ceramic brake disc
WO2017107735A1